Biology, venom composition, and scorpionism induced by brazilian scorpion Tityus stigmurus (Thorell, 1876) (Scorpiones: Buthidae): A mini-review. (15th October 2020) - Furtado, Allanny Alves; Daniele-Silva, Alessandra; Silva-Júnior, Arnóbio Antônio da; Fernandes-Pedrosa, Matheus de Freitas
Abstract: Scorpionism is a serious public health problem in various regions of the world. In Brazil, a high number of accidents by scorpions have been reported. From 2014 to 2018, about 547, 000 cases were recorded, resulting in 466 deaths. The scorpion Tityus stigmurus is the predominant species in the northeast of Brazil, being responsible for most scorpionism cases in this region. With the aid of the transcriptomic approach of the venom gland of this species, components as neurotoxins, antimicrobials, metal chelating peptides and hypotensins, have been identified and characterized in silico, showing different biologic activity in vitro . In addition, the neuronal, pancreatic, renal, and enzymatic effects have been demonstrated for the crude T. stigmurus venom. Therefore, the T. stigmurus scorpion venom constitutes a rich arsenal of bioactive molecules with high potential for therapeutic and biotechnological application. Highlights: T. stigmurus is the major cause of accidents in northeastern Brazil. The venom is one of the most lethal for mices among Brazilian species. The venom causes neuronal, pancreatic, renal damage, and has enzymatic properties. The venom has neurotoxic, antimicrobial, hypotensive and metal chelating molecules. Components of the venom have evident biotechnological and therapeutic potential.